(untitled) (Integral Research, 2025)
The Indian knowledge tradition is a pure, serene, and sacred stream that embodies the faith, values, ideals, philosophy, wisdom, culture, civilization, ethics, methodologies, actions, energy, and vibrant emotions of sages and seers. This tradition is not limited to a single principle but represents a vast ideology that encompasses the knowledge ingrained in every particle of India. Like the eternal radiance of the hymns of the ishis, this knowledge tradition carries within it countless streams of wisdom—each flowing in its own course while also intertwining with others, amplifying their brilliance. This very luminous essence is the Indian knowledge tradition. If we glimpse the reflection of Hindi literature in this flowing stream of knowledge, it appears radiant, like a stream of ghee (clarified butter). What exactly is the Indian knowledge tradition? The moment this curiosity arises, the mind instinctively turns to the Vedas, for they are the very foundation of Indian culture, wisdom, and civilization. From them emerged all languages and all forms of knowledge. Hindi, often regarded as the daughter of Sanskrit, carries forward this wisdom through various literary forms, reaching every seeker. Upholding this knowledge tradition, Hindi literature continues to advance on its path of duty. Indian knowledge traditions, enriched by Hindi literature, have always embodied the essence of democracy, continuously imparting a sense of completeness to the world. Their influence permeates every sphere globally. Ancient life values, the Panchamahayajnas (five great sacrifices), sanskāras (rituals), the three debts (Rinatraiya), Indian Ayurvedic practices, the Indian education system, Vedic wisdom, the domestic sciences of the Upanishads, the practical knowledge enshrined in the Puranas, the untapped reservoirs of skill, the Ashtanga Yoga disciplines that shape physical and mental well-being, the invaluable nourishment for nature embedded in Indian literature, the ideologies of health and preservation, and the spiritual energies pervading philosophical schools—all these manifest as diverse powers, spreading the fragrance of Indian knowledge traditions across the world. They form the foundation of Western cultures, knowledge systems, research, and rituals, illuminating the world like beams of beauty. Within these knowledge traditions, Hindi literature has consistently presented unique and remarkable examples. Even today, the stream of wisdom flowing from Hindi literature has the power to uplift and sanctify every heart.